Photosynthesis of Au8Cu6 nanocluster for photocatalysis in oxidative functionalization of alkynes - Yan Zhao; Ze-Min Zhu; Weigang Fan; Wanli Zhu; Jing-Jing Yang; Yang Tao; Wenwen Fei; Hong Bi; Sheng Zhang; Man-Bo Li (Nature Communications)
Abstract Ligand-protected metal nanoclusters provide an ideal platform for investigating photoredox catalysis. The central challenge is balancing their stability and catalytic activity. Here we show a photochemical reduction–oxidation cascade method for synthesizing an Au8Cu6 nanocluster, which features a robust structure and active surface. Photoredox catalytic activity of Au8Cu6 is developed for the functionalization of alkynes under oxidative conditions. Mechanism studies based on the precise structure reveal the catalytic process of the Au8Cu6 nanocluster. Oxidant-dependent selectivity of Au8Cu6 catalysis is developed for chemodivergent synthesis of mono- and di-functionalized products in high efficiency. The results will stimulate more research on metal nanocluster synthesis and catalysis.